The Development of Mortgage Finance in Nigeria and its Impact on the Economy - Siyan, Peter; Adegoriola, Adewale E; Erivwode, Ovosa Mercy (International Multilingual Journal of Science and Technology, 2019)
This study examines the development of mortgage finance in Nigeria and its impact on economic growth. Aggregate housing finance data for by both banks and non-financial institutions was used to measure housing finance. Other variables considered include financial debt proxy by M2Per capita, financial instability proxy Interest rate and the level of development of the capital market measured by market capitalization. Time series data covering the period 1990-2016 was obtained from Central Bank statistical bulletin, National Bureau of Statistic and World Bank. The methodology adopted in the study is Vector Autoregressive Model (VAR) was estimated using linear regression method. The results of the analysis indicated that there is a one-way causal link runs from mortgage finance to economic growth. In addition, mortgage finance was found to be a significant determinant of increasing pattern of economic growth over a long period of time. Due to the level of the country’s financial depth, it was recommended that Nigerian government should intensify effort aimed at consolidating the level of financial re-structuring in the non-financial sector which mortgage financing belong. The central bank should make a policy stipulating commercial banks to set aside certain proportion of their total assets to finance housing demands.
Keywords: Economic growth; Hypothèque; Mortgage Finance; Vector Autoregressive

A contract theory approach to Islamic financial securities - Hanif Arbi, Lukman (La Trobe University, 2018)
The aim of this thesis is to investigate the economic and financial substance of certain contractual requirements imposed by Islamic commercial law as well as some of their implications. More attention is given to requirements that have financial implications and are related to those discussed in the contract theory literature. We divide our investigation into four parts. The first part is an examination of the fundamental transactional requirements in Islamic commercial law, focusing on those related to four primary Islamic Financial Securities (IFSs). In the second part, we use our findings to construct an alternative asset pricing methodology. We also explore our findings in the third and fourth parts using the principal-agent model of Holmström and Milgrom (1991). More specifically, we use it to respectively model the relationship between underwriters and Islamic commercial law regulators as well as consider the case of ambiguous incentive contracts. Each part of our investigation has yielded substantial contributions to the literature as follows. Firstly, our examination of Islamic commercial law principles and contracts reveals that there are indeed legal requirements which have direct implications for financial models, such as the need for a liquidity discount in receivables-based ṣukūk as they are – in principle – non-tradeable. Secondly, the asset-pricing model we have constructed allows us to examine the equilibrium return and investment levels of IFSs. This allows us to derive conditions at which one security yields higher returns than another. Thirdly, our cooperation model suggests that cooperation between underwriters and Islamic commercial law regulators is only beneficial for an issuer of a structured Islamic financial product if their synergy benefits are over a certain level. Lastly, our investigation into ambiguous incentive contracts demonstrates that it is never beneficial for principals to offer such contracts to ambiguity averse individuals as it unambiguously reduces the principal’s profit.

Stuck in a time warp: security interests in chattel mortgages and the bills of sale legislation in Nigeria - Otabor-Olubor, Iyare (International Company and Commercial Law Review, 2015)
IRep - Nottingham Trent University's open access institutional research repository

Establishing an international registration system for the assignment and security interest of receivables - Jon, Woo-Jung (Oxford University, 2014)
Legal systems around the world vary widely in how they deal with the assignment of receivables. This legal variety makes it difficult for financiers to conduct their international receivables financing business. This thesis suggests an International Registration System for the Assignment and Security Interest of Receivables (‘IRSAR’) and proposes a model international convention for the IRSAR (‘proposed IRSAR Convention’), which could help financiers to overcome the obstacles they currently encounter. Under the proposed IRSAR Convention, the international assignment of receivables would be regulated by a unified legal system with respect to priority and perfection. The IRSAR would facilitate international project financing. Furthermore, the IRSAR would enable companies to raise finance from greater ranges of investors around the world through international receivables financing and to dispose of non-performing loans more easily. The proposed IRSAR Convention would succeed the UN Convention on the Assignment of Receivables in International Trade in the attempt of establishing a registration system for international assignments of receivables. The proposed IRSAR Convention confines its scope of application by defining the assignor (or the security provider), inventing the concept of ‘Vehicle for the International Registration System’ (‘VIRS’). The proposed IRSAR Convention applies where the assignor or security provider is a VIRS. An assignment of a receivable where the assignor is a VIRS and a security interest in a receivable where the security provider is a VIRS could be registered in the IRSAR. Under the proposed IRSAR Convention, priority of assignments of and security interests in receivables is determined by the order of registration in the IRSAR. The proposed IRSAR Convention would be a receivables version of the Cape Town Convention. With respect to the contents and effect of registration, it would prescribe a notice-filing system along the lines of that adopted in the UCC Article 9. With respect to the operation of the registration, it would adopt an automatic online registration system operating 24 hours a day, 365 days a year like the International Registry under the Cape Town Convention.
Keywords: Comparative law; Contract; Property law; Restitution; Tort